Conjugated polymers and oligomers : structural and soft matter aspects - Knaapila, Matti (World Scientific Publishing Co. Pte. Ltd., 2018)
"This book identifies modern topics and current trends of structural and soft matter aspects of conjugated polymers and oligomers. Each chapter recognizes an active research line where structural perspective dominates research and therefore the book covers fundamental aspects of persistent conjugated polymer backbone, water soluble conjugated polyelectrolytes and surfactants, conjugated molecules and biomolecules and DNA and the advanced use of synchrotron radiation and electron microscopy to find out structural details in conjugated molecule films and devices as well as under ambient and extreme conditions"- Resumé vydavatel
Keywords: polymery; polymers; konjugované polymery; oligomery; kolektivní monografie; elektronické knihy; collective monographs; electronic books